The role of single trial variability in event related potentials in children with attention deficit hyperactivity disorder. (May 2023) - Arnett, Anne B.; Gourdet, Gaelle; Peisch, Virginia; Spaulding, Katherine; Ferrara, Erica; Li, Vivian
Highlights: Children with high ADHD symptom severity consistently have reduced amplitude of the grand average P3 event related potential. This association is largely explained by reduced peak amplitude in the P3 time window across trials. Single trial variability in peak P3 latency across trials explains additional variance in the association between ADHD symptoms and grand average P3. Abstract: Objective: Children with attention deficit hyperactivity disorder (ADHD) show attenuated mean P3 component amplitudes compared to typically developing (TD) children. This finding may be the result of individual differences in P3 amplitudes, P3 latencies, and/or greater single trial variability (STV) in amplitude or latency, suggesting neural "noise." Methods: Event related potentials (ERPs) from 75 children with ADHD and 29 TD children were recorded with electroencephalography (EEG). Caregivers provided ratings on child ADHD symptoms. Single-trial ERP amplitudes and latencies were extracted from the P3 component time window during a visual oddball task. Additionally, we computed individual-centered and trial-centered P3 amplitudes to account for inter-individual and inter-trial variability in the timing of the P3 peak. Results: In line with prior research, greater ADHD symptom severity was associated with reduced mean P3 amplitude. This correlation was no longer significant after correcting for inter-trial differences in P3 latency. In contrast, greater ADHD symptom severity was associated with reduced STV in P3 amplitude. Conclusions: Our results suggest that attenuated average P3 amplitude in ADHD samples is due to a consistent reduction in strength of the neurophysiological signal at the single trial level, as well as increased inter-trial variability in the timing of P3 peak amplitudes. The traditional method of extracting P3 amplitudes based on a single time window for all trials may not adequately capture variability in P3 latencies associated with ADHD. Significance: Inter- and intra-individual differences in brain signatures should be considered in models of neurobiological differences in neurodevelopmental samples.